MENULIS CERPEN DENGAN METODE TATAP HOPBOT PADA MASA COVID - 19 - M.TH.E RINA LISTIANA (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2022)
The COVID -19 pandemic could lead many problems on learning process for teacher and student’s parents, that why we need proper strategy during the leasson to solve thus problems. The learning outcomes during the COVID -19 pandemic on the short story writing skills of Class IXA students can satisfy teachers and make parents proud. Lesson problems during this pandemic can be solved with the innovative methods provided by the teacher. The method which is used by the teacher is Tatap Hopbot in short story writing lessons. This research is a Best Practice research from learning how to write short stories for students of class IXA. Thei results of this study indicate that besides learning, students become more motivated and enthusastic to participate in write short stories lesson in virtual class. Students are able to develop the material, not only based on teacher material but also parents have involved in the development of learning, especially in short story subjects. The results of this Best Practice research have proven that there is an increase in achievement in learning to write short stories which can be seen in the difference in the average results from pre-writing or pre-test 76 to post-test 83. Thus, it is proven that there is an increase in results of 7 or 0.9%. ABSTRAKPermasalahan pembelajaran di rumah atau online di masa pandemi covid-19 memang menjadikan risau bagi guru, peserta didik, dan khususnya orang tua. Salah satu penyelesaian permasalahan adalah guru perlu menemukan metode yang cocok dalam pembelajaran di masa ini. Dari hasil pembelajaran masa pandemi covid-19 pada keterampilan menulis cerpen peserta didik Kelas IXA, guru dapat merasa puas dan membanggakan orang tua. Hal ini dikarenakan dapat terselesaikan dengan adanya metode inovatif yang diberikan guru. Metode yang digunakan guru adalah Tatap Hopbot pada pelajaran menulis cerpen.Dengan demikian, penelitian ini merupakan sebuah penelitian Best Practice dari pembelajaran menulis cerpen peserta didik kelas IXA. Hasil penelitian ini menunjukan selain pembelajaran sangat memotivasi peserta didik dalam belajar dan menjadikan lebih semangat sehingga kelas virtual menjadi hidup. Peserta mampu mengembangkan materi, dan tidak tepaku pada guru karena pada pembelajaran ini, peran orang tua terlibat dalam perkembangan belajar. Hasil penelitian Best Practice ini terbukti ada peningkatan prestasi dalam pembelajaran menulis cerpen yaitu terdapat pada perbedaan rata-rata hasil dari pra menulis atau pretes 76 dengan postes 83. Dengan demikian, terbukti adanya peningkatan hasil 7 atau 0,9%.